KNOWLEDGE, ATTITUDE AND PRACTICE OF MOTHERS TOWARDS PREVENTION AND HOME BASED MANAGEMENT OF DIARRHEAL DISEASE IN UNDER 5 YEARS CHILDERN (Journal of Medical & Health Sciences Review, 2025)
Background:Diarrhea continues to be the third leading cause of death among children under the age of five worldwide, it kills more young lives. However, many of these deaths could be prevented through the basic home-based care, such as  used of oral rehydration therapy. Mothers play a key role in both the prevention and management of the diseases. Therefore, the primary aim of this study was to evaluate the knowledge, attitudes, and practices of mothers regarding the prevention and home based  management of diarrheal disease in children under five year in Khuda Ji Basti, Kotri, Jamshoro Sindh.Methodology:Current community based cross-sectional study was conducted at the Khuda Ji Basti, Kotri, Jamshoro Sindh, Pakistan. Mother of children under 5 years of age and suffering from diarrhea were included in the study. Total 200 mothers were interviewed by using questionnaires, adopted and modified  comprising of 26 questions.1st  Demographic information, section 2 knowledge,  section 3 attitude, and section 4 practice regarding diarrhea management. Data was entered and analyzed used SPSS  23.00 v.Results:In this study, 200 participants were included with 100% response rate. From total 200 mothers, around two-thirds (75.2%) of them had good knowledge, and  p value was (0.002). Mothers  (55%) were positive attitude towards home-based management and prevention of diarrhea among under-five children, p value was  (0.065). Regarding the attitude of the mothers, 78% were  poor practice towards home-based management and prevention of diarrhea among under-five children, p value was (0.106).ConclusionThe study indicated that mothers were a satisfactory level of knowledge regarding the prevention and home-based management of diarrheal diseases in children under five. They were generally aware of key practices such as breastfeeding, and was used of oral rehydration solutions (ORS), handwashing, sanitation, and hygiene. However, despite this knowledge, proper hygiene was not consistently observed among the mothers and childrens. Additionally  many families continued to used contaminated water, and most mothers were not received guidance from healthcare professionals.